Associations Between Body Fat Percentage and Fitness among Police Officers: A Statewide Study - John M. Violanti; Claudia C. Ma; Desta Fekedulegn; Michael E. Andrew; Ja K. Gu; Tara A. Hartley; Luenda E. Charles; Cecil M. Burchfiel (Elsevier, 2017)
Background: Police work is generally sedentary although there may be situations that require physical endurance and strength, such as foot chases and arresting suspects. Factors such as excessive body fat can impede an officer's physical ability to deal with such occurrences. Our objective was to examine associations between officers' body fat percentage (BF%) and performance on a standardized fitness protocol. Methods: Data were obtained from fitness screening among 1,826 male and 115 female officers in a large US police agency. The screening consisted of a 2.4-km run, push-ups, sit-ups, and sit-and-reach test. Sex-specific body fat percentages were estimated from skinfold thickness measured using calipers. Linear regression models were used to examine unadjusted and adjusted mean scores of fitness tests across BF% tertiles. Results: The prevalence of overall fitness was 4.3 times greater in male officers and 3.6 times greater in female officers having the lowest BF% tertile compared with the highest tertile (30.3% vs 7.1% and 46.0% vs 12.8%, respectively). BF% was linearly and positively associated with the time of 2.4-km run (p<0.001), and linearly and inversely associated with the number of push-ups (p<0.001), sit-ups (p<0.001), and the distance of sit-and-reach (p<0.001) in men. Similar associations were observed in women with the exception of sit-and-reach (p=0.122). Associations were independent of age, race/ethnicity, rank, and duty station. Conclusion: Overall, BF% was inversely associated with fitness levels in male and female officers. Future longitudinal studies should be initiated to explore the potentially causal relationship between BF% and fitness in law enforcement officers.